Analysis of the variation pattern in left upper division veins and establishment of simplified vein models for anatomical segmentectomy - Zhang, Min (Ann Transl Med, 2020)
BACKGROUND: Three-dimensional computed tomography bronchography and angiography (3D-CTBA) is a powerful tool to analyze pulmonary anatomy. We used 3D-CTBA to analyze variations of the pulmonary veins of the left upper division (LUD) and created a simplified LUD vein model. METHODS: Between January 2019 and October 2019, 124 patients with left-sided pulmonary lesions were admitted and underwent 3D-CTBA prior to surgery. We reviewed the anatomical variations of the LUD veins in these patients using 3D-CTBA images and classified them according to their position in relation to the bronchus. To facilitate this process, the same nomenclature as that used to describe the veins of the right upper lobe (RUL) is used for the LUD. RESULTS: The pattern of LUD veins could be classified into three forms: an anterior + central form, an anterior form and a central form. For the central form, V (1+2) a, V (1+2) b, V (1+2) c and V (1+2) d drained into V. cent. For the anterior form, V (1+2) d drained into V. ant. The anterior + central form could be further classified into three subtypes (V abc, V ab and V a). CONCLUSIONS: This is the first report to categorize the pattern of veins in the LUD. This may facilitate the creation of simplified models for use in pre-operative planning for segmentectomy.